Adverse events of tumor necrosis factor alpha inhibitors for the treatment of ankylosing spondylitis: A meta-analysis of randomized, placebo-controlled trials - Feng, Haihuan; Zhao, Ying; Kuang, Weihong; Dai, Yanping; Cen, Xiaobo; Qin, Feng (Frontiers in Pharmacology, 2023)
Objective: Tumour necrosis factor alpha inhibitors (TNFi) have shown substantial efficacy in alleviating and treating ankylosing spondylitis (AS). However, the heightened interest is accompanied by concerns over adverse events. In this meta-analysis, we analyzed both serious and common adverse events in patients treated with TNFi compared with those in placebo group. Methods: We searched clinical trials from PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure, Wanfang Data and Vip Data. Studies were selected based on strict inclusion and exclusion criteria. Only randomized, placebo-controlled trials were included in the final analysis. RevMan 5.4 software was used for meta-analyses. Results: 18 randomized controlled trials recruiting 3564 patients with AS were included, with overall moderate to high methodological quality. Compared with placebo, the incidences have no difference and numerically were only slightly increased for serious adverse events, serious infection, upper respiratory tract infection and malignancies in patients treated by TNFi. While TNFi treatment significantly increased the incidence of overall adverse events, nasopharyngitis, headache and injection-site reactions in AS patients when compared with placebo. Conclusions: The available data indicated that the AS patients who received TNFi had no significantly increased risks of serious adverse events when compared with placebo. However, TNFi significantly increased the incidence rate of common adverse events, including nasopharyngitis, headache and injection-site reactions. Large-scale and long-term follow up clinical trials are still necessary to further investigate the safety of TNFi in AS treatment.